2022
DOI: 10.1016/j.euo.2021.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Staging 18F-fluorodeoxyglucose Positron Emission Tomography/Computed Tomography Changes Treatment Recommendation in Invasive Bladder Cancer

Abstract: Given the high risk of systemic relapse following initial therapy for muscle-invasive bladder cancer (MIBC), improved pretreatment staging is needed. We evaluated the incremental value of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG-PET/CT) after standard conventional staging, in the largest cohort of MIBC patients to date. This is a retrospective analysis of 711 consecutive patients with invasive urothelial bladder cancer who underwent staging contrastenhanced CT (chest and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…The highest uptake was obtained by liver metastases (n = 6) and equally by peritoneal carcinomatosis (n = 16) with a mean SUVmax of 9.8. Strong uptakes were also determined in lymph node metastases (n = 36) with a mean SUVmax of 8.7, bone metastases (n = 22) showing a mean SUVmax of 7.8, lung metastases (n = 6) with a mean SUVmax of 5.0, and other metastases (n = 2) with a mean SUVmax of 5.2 (Fig. 1a).…”
Section: Biodistribution and Uptake In Tumor Lesionsmentioning
confidence: 87%
See 1 more Smart Citation
“…The highest uptake was obtained by liver metastases (n = 6) and equally by peritoneal carcinomatosis (n = 16) with a mean SUVmax of 9.8. Strong uptakes were also determined in lymph node metastases (n = 36) with a mean SUVmax of 8.7, bone metastases (n = 22) showing a mean SUVmax of 7.8, lung metastases (n = 6) with a mean SUVmax of 5.0, and other metastases (n = 2) with a mean SUVmax of 5.2 (Fig. 1a).…”
Section: Biodistribution and Uptake In Tumor Lesionsmentioning
confidence: 87%
“…68 Ga-FAPI-PET/CT in patients with urinary tract cancer presented a rather strong mean uptake (SUVmax 9.5) as well. For staging purposes, the European Association of Urology guidelines currently recommend contrast-enhanced CT of the chest and abdomen/pelvis [ 21 , 22 ]. However, conventional CT has some limitations due to imprecise determination of the tumor allocation, extent, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…68 Ga-FAPI PET/CT in patients with urinary tract cancer, presented a rather strong mean uptake (SUVmax 9.5) as well. For staging purpose, the European Association of Urology guidelines currently recommends contrast-enhanced CT of the chest and abdomen/pelvis (19,20). However, conventional CT has some limitations due to imprecise determination of the tumor allocation, extent and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…A 18 F-FDG-PET/CT is performed for staging purposes prior to NAC, given the incremental value of metabolic information over morphological CT, for assessing lymph node and distant metastases at diagnosis of MIBC [32,33]. In a recent study, it was reported that a staging 18 F-FDG-PET/CT after a conventional diagnostic CT thorax and abdomen changed treatment recommendations in 18% of cases, 9% of which changed from potential curative treatment to palliative treatment due to detection of distant metastases [34]. However, the superiority of 18 F-FDG-PET/CT over conventional CT scanning for clinical response evaluation during NAC has not yet been proven.…”
Section: Pre-operative Stagingmentioning
confidence: 99%